The Perbedaan pengetahuan gizi, status gizi, dan produktivitas kerja pada tenaga kesehatan dan non-kesehatan : Indonesia - Laras Sitoayu; Leyrina Rizky Utami; Lintang Purwara Dewanti; Putri Ronitawati; Yulia Wahyuni (UHAMKA PRESS, 2022)
Nutrition for female workers has an important role, both for welfare and in order to increase discipline and productivity. Female workers are very prone to nutritional problems because the characteristics of female workers are different from that of male workers. This study aimed to determine the differences in nutritional knowledge, nutritional status and work productivity of female health workers (nakes) and female non-health workers (non-nakes) at RSIA Sammarie Basra, East Jakarta. This type of research is a quantitative study with adesign cross sectional. Subjects were 62 people consisting of 31 female nakes and 31 female non-nakes who were taken using the two difference test technique independent mean. Data collection was carried out by means of questionnaires and anthropometric measurements. Data analysis used independent t-test. Results: the average nutritional knowledge of the subjects was 62,65 (sufficient), nutritional status was 24,7 (normal), work productivity was 107,94 (sufficient). The significant variables were knowledge of nutrition and nutritional status; and the non-significant variable was work productivity. Conclusion: there were differences in nutritional knowledge and nutritional status for female health workers and female non-health workers, but there was no significant difference in work productivity for female health workers and female non-health workers at RSIA SamMarie Basra